VIRTUAL REALITY AND DENTISTRY - BHATNAGAR, ANAND; BHATNAGAR, EVA (International Journal of Current Pharmaceutical Research, 2023)
The field of dentistry could benefit considerably from virtual reality (VR). There will be several ways like Virtual reality can be used to teach patients about oral hygiene and dental procedures in a more dynamic and engaging way. Patients can utilize virtual reality (VR) to learn about various dental procedures, view 3D representations of their teeth and gums and comprehend how poor oral hygiene affects their general health. Many people experience fear or worry when going to the dentist, which can prevent them from getting the essential dental care. VR can reduce these anxieties by fostering a more tranquil and immersive atmosphere. For instance, patients might utilize virtual reality (VR) headsets to divert their attention during treatments or imagine serene settings to lessen anxiety. Virtual reality can also be utilized to educate and teach dental practitioners in a more effective and efficient manner. Before working on actual patients, students can perform a variety of dental operations in a virtual setting, which helps them develop their confidence and competence. VR can be used by dental practitioners to learn about new methods, instruments, and technologies. In general, the use of virtual reality in dentistry has the potential to enhance dental professional training and education, patient results, and patient involvement and satisfaction.